Revealing Femmegimp: A Sex-positive Reflection on Sites of Shame as Sites of Resistance for People with Disabilities - Erickson, Loree (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This paper, which doubles as a call to action, draws on my personal experience, theoretical analysis, and sexually explicit self-portraiture to produce a sex positive reflection locating sites of shame as sites of resistance to western society's conceptualization of the body, regarding dependency, vulnerability, touch, and sexuality.